Helicobacter pylori delays neutrophil apoptosis but also drives the formation of cells with a leaky plasma membrane: Implications for inflammation - Thai, Tran Duong; Kamsom, Chatcharin; Phoksawat, Wisitsak; Nithichanon, Arnone; Faksri, Kiatichai; Sripa, Banchob; Edwards, Steven W.; Salao, Kanin (Molecular immunology, 2025)
Opisthorchis viverrini (OV)-induced cholangiocarcinoma (CCA) is a significant public health concern in countries in the Lower Mekong Basin. OV is a reservoir for Helicobacter pylori (H. pylori), and so many individuals are co-infected with these two biological carcinogens. Our study aimed to investigate interactions between H. pylori isogenic strains possessing or lacking the pathogenicity factor CagA (cagA+ and cagA-) with neutrophils. Both H. pylori strains were co-cultured with neutrophils in vitro, and neutrophil activation, phagocytosis, reactive oxygen species (ROS) production, and cell survival/apoptosis were measured. Both isogenic strains of H. pylori stimulated phagocytosis and while the cagA- strain induced slightly higher ROS production, both strains served as potent activators of neutrophils. Notably, H. pylori induced rapid cell death in a sub-population of neutrophils after 30 min of co-incubation while extending the lifespan of the neutrophils that survived this initial cell death. This initial incubation resulted in the appearance of propidium iodide (PI)+ neutrophils, i.e. cells with a compromised plasma membrane that could result in the release of inflammation-promoting neutrophil contents. While significantly more viable neutrophils were detected after 24 h (and 48 h) incubation with H. pylori, those cells that did not survive also showed characteristics of a compromised plasma membrane (i.e. PI+). We propose that the combinations of PI+ neutrophils with leaky plasma membranes and non-apoptotic neutrophils with enhanced survival after incubation with H. pylori may drive persistent inflammation. These findings offer new insights into the immunopathogenesis of OV and H. pylori co-infections, which may help improve OV treatment strategies. •cagA+ and cagA- H. pylori extended the lifespan of neutrophils following phagocytosis.•These H. pylori strains induced rapid death of neutrophils by late-apoptosis/necrosis.•H. pylori-infected neutrophils with a leaky plasma membrane can result in persistent inflammation.